Български типографски практики в текстовия дизайн на буквара и читанката за първи клас през ХХ век [Bulgarian typographic practices of text design, observed in the 20th century primer and 1st grade reader] - Stoyanova, Maya (Годишник на Софийския университет „Св. Климент Охридски”, Факултет по журналистика и масова комуникация [Annual of Sofia University „St. Kliment Ohridski”, Faculty of Journalism and Mass Communication], 2017)
The article investigates the tendencies of the 20th century Bulgarian typographic practices, applied in the primers and 1st grade readers, published in the period 1900 – 2014. A graphic analysis of the typographic design and the typeface design of Bulgarian textbooks in reading literacy for children is done and presented in the paper.
https://katalog.adlr.link/Record/ai-53-585278